Mode tracking and diagnosis of hybrid systems, an integrated approach - Arogeti, Shai A. (2013)
In this paper, we integrate information from a hybrid bond graph (HBG) model and discrete event systems (DES) into a fault diagnosis method for hybrid systems. In a pure HBG framework, mode change detection and isolation is handled by the mode change signature and the mode change signature matrix. In a DES approach, discrete states and faults are traced based on observable events and diagnosers. The integration of the two approaches is based on a new diagnoser that is driven by both, observable events and consistency indicators generated by continuous residuals. The proposed method allows not only to effectively trace the system mode, but also to decide whether this mode is faulty or normal. The new method is presented along with a theoretical example.